Keberadaan Tari Tarea-Readi Kenagarian Koto Gadang Guguk Kecamatan Gunung Talang Kabupaten Solok - Sri Wahyuni; Herlinda Mansyur (SENDRATASIK UNP, 2019)
This article aims to reveal and describe the existence of Tarea-rea dance in Kenagarian Koto Gadang Guguk Kecamatan Gunung Talang  Kabupaten Solok. This type of research is qualitative research with a descriptive method. The main instrument of this research is its own research and assisted with supporting instruments such as stationery, cameras and Handycam.  Data types use primary data and secondary data. Data collection techniques are conducted by way of library studies, observations and interviews. The steps for analyzing data are data collection, analyzing data, describing data and making conclusions. The results showed that Tarea-rea dance is a art carried by the ancestors of the Guguk people who inherited hereditary with the traditional system. Tarea-rea dance was originally used as a dance at the time of the decline ceremony of rice harvesting. Since 2015 This dance is increasingly popular in the Kenagarian Koto Gadang Guguk as the performing arts. The existence of Tarea-rea dance is still recognized and cultivated by the community and local people also have recognized the existence of the dance in the Kenagarian Koto Gadang Guguk.